Hubungan Stres Kerja dengan Unsafe Action pada Pekerja Konstruksi di PT. X Kota Surabaya - Achmad Helmi; Nilam Puspitasari; Tri Martiana; Indriati Paskarini; Yustinus Denny Ardyanto Wahyudiono; Mitha Qurrota Ayuni (Universitas Airlangga, 2023)
Background: Each work, formal or non-formal, at ocean, on arrive, or within the discuss includes a chance of work mischances, counting development work at PT. X city of Surabaya. Risky activity is one of the things that causes push and work mischances as the most person viewpoints that cause work mischances. Purpose: This investigate points to analyze the relationship of risky activity with work stretch in one of the development companies at PT. X City of Surabaya. Methods: This investigate may be a quantitative investigate employing a expressive approach and a cross-sectional think about plan where the test is 30 specialists. The autonomous variable within the taking after investigate is risky activity whereas the subordinate variable is work stretch. Information investigation utilized the chi square factual test with a centrality constrain of α = 0.05. Result: The comes about of the bivariate test clarified that there was a relationship between work stretch and risky activity (p-value = 0.001) in development specialists at PT. X in Surabaya City. Conclusion: It can be concluded that there's a relationship between work push and hazardous activities in development laborers at PT. X in Surabaya City.